PENINGKATAN KEMAMPUAN BERBICARA MELALUI TELEPON DENGAN METODE BERMAIN PERAN SISWA KELAS IV NEGERI 1 TEUBENG - Nanda Saputra (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2017)
The problem in the research is that the implementation of Indonesian language learning in SD Negeri Teubeng is not optimal, especially for fourth grade students. From the observations obtained, that in the implementation of teaching and learning activities the teacher has not been able to develop students' awareness of self-confidence in learning. Most of the students were afraid so they did not dare to speak about mastering the language. The problem of this classroom action research is whether the ability to speak by telephone can be improved by using the role-playing method in class IV SD Negeri 1 Teubeng. The aim of the study was to improve students' speaking skills by telephone by using the role-playing method in the fourth grade of SD Negeri 1 Teubeng. The subjects in this study were all fourth grade students, totaling 32 people. Data collection techniques carried out in this study were teacher activity observation sheets and student activity observation sheets during the implementation of learning through the role playing method and the results of the cycle action test. This research is a classroom action research (CAR). This research was conducted in two cycles. Based on the results of this classroom action research, it shows a gradual increase in each cycle. From the results of the first cycle of action research, the average value of students was 67.5% with classical learning completeness of 68.75%, then in the second cycle, the average value increased to 76.04% with classical completeness of 87.5 %. Based on these results, it can be concluded that through the role playing method, fourth grade students of Negeri 1 Teubeng can improve their speaking skills by telephone in learning Indonesian